2016
DOI: 10.1007/s00410-016-1262-8
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific hydrogen diffusion rates during clinopyroxene dehydration

Abstract: peaks at 3620, 3550, 3460, and 3355 cm −1 in the thickness direction at 800 °C. Bulk hydrogen diffusivity in the Jaipur diopside is consistent with previous work, and hydrogen diffusivity in augite PMR-53 is slightly lower than the fast direction diffusivities measured || [100] and [001]* in Jaipur diopside. Both diopsides show 1-2 orders of magnitude differences in the peaks-specific diffusivities, with the fastest diffusivities at 3450 cm −1 and the slowest at 3645 cm −1 . However, the hydrogen diffusivities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 81 publications
4
35
1
Order By: Relevance
“…Based on diffusion data for proton‐vacancy exchange in olivine (Demouchy & Mackwell, ), the starting material used in this study would be fully hydroxylated (≥95%) after 168 h even at 750°C. Similar results are found for orthopyroxene (Stalder & Skogby, ), whereas mantle clinopyroxene and garnet should reequilibrate even faster (e.g., Ferriss et al, ). Recent experiments by Jollands et al () demonstrate, however, that this kind of hydroxylation using highly mobile proton‐(magnesium) vacancy preserves metastable configuration of defects out of equilibrium from externally imposed silica activity or oxygen fugacity conditions.…”
Section: Discussionsupporting
confidence: 60%
“…Based on diffusion data for proton‐vacancy exchange in olivine (Demouchy & Mackwell, ), the starting material used in this study would be fully hydroxylated (≥95%) after 168 h even at 750°C. Similar results are found for orthopyroxene (Stalder & Skogby, ), whereas mantle clinopyroxene and garnet should reequilibrate even faster (e.g., Ferriss et al, ). Recent experiments by Jollands et al () demonstrate, however, that this kind of hydroxylation using highly mobile proton‐(magnesium) vacancy preserves metastable configuration of defects out of equilibrium from externally imposed silica activity or oxygen fugacity conditions.…”
Section: Discussionsupporting
confidence: 60%
“…In contrast, studies on natural samples reveal that pyroxenes may preserve the initial water content [ Peslier et al ., ; Bonadiman et al ., ; Soustelle et al ., ; Gose et al ., ; Warren and Hauri , ; Bizimis and Peslier , ; Chin et al ., ]. A possible explanation for these observations is that H diffusion operates by the fast “proton‐polaron” mechanism in mantle olivine, much faster than in Cpx [ Ferriss et al ., ]. However, it was recently reported that natural Opx in peridotite xenoliths may also lose some water during ascent and cooling [ Tian et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…The alternative is to directly analyze water in nominally anhydrous mantle minerals of dismembered peridotite bodies (e.g., Miller et al, 1987). Experiments have shown that the substitution type by which hydroxyl is bound in a mineral's structure has a major impact on the diffusivity of hydrogen and, thus, the tendency toward water loss or gain (Blanchard & Ingrin, 2004;Ferriss et al, 2016;Hercule & Ingrin, 1999;Koch-M€ uller et al, 2007;. The greatest problem-water loss due to decompression-applies to any approach because water loss may affect both mantle minerals and melts (plus melt inclusions).…”
Section: General Backgroundmentioning
confidence: 99%
“…Second, it is also possible that kinetic reasons limit or even inhibit water loss in saturated minerals. Experiments have shown that the substitution type by which hydroxyl is bound in a mineral's structure has a major impact on the diffusivity of hydrogen and, thus, the tendency toward water loss or gain (Blanchard & Ingrin, 2004;Ferriss et al, 2016;Hercule & Ingrin, 1999;Koch-M€ uller et al, 2007;. In addition, hydrogen diffusivity also depends on the mineral species.…”
Section: General Backgroundmentioning
confidence: 99%